Henrique Oswald's Etude n degrees 2 in C Minor: The inconsistencies between the manuscript and the nationalist version - Marun, Nahim [UNESP] (Univ Federal Goias, 2019)
This article presents an analysis of the rhythmic and harmonic differences found between the only available edition and the manuscript of the Etude n degrees 2 in C minor, from the set of Trois Etudes for solo piano by Henrique Oswald. The developed hypothesis is that Bevilacqua Edition of this work was a nationalist idiosyncrasy, imposed in some extent, over the composer's style. The conclusion is that the edition, which was perpetuated by several recordings, has harmonic mistakes and adulterated brazilian rhythms, which resulted forced and have no musical sense within the composer's style. These rhythms were exalted by several nationalist authors, but they fit musically oddly regarding the unity of Trois Etudes as a whole, and the coherence of Oswald's piano aesthetics.
Keywords: Henrique Oswald's Etudes for Piano; Trois Etudes; Etude n degrees 2 in C minor; Manuscripts and editions inconsistencies